Revitalization of Adolescent Curiosity of Students - Vichalkovskaya, N. K. (Psychological Prospects Journal, 2011)
The article is dedicated to the problem of the curiosity forming of adolescent-students. The psychological structure of adolesents’ curiosity is defined, levels of its develop-ment are clarified on the basis of intensity and variety indices. Psychologic-pedagogical conditions and means of the activization students’ curiosity development are described.
Keywords: curiosity; formation; activization; the components of curiosity; the psyhological structure; metaphor